Evaluation of The Cloud Computing Training Program for Management of Collaborative Learning Document - Harjito, Harjito; Amalina, Nur Dina; Nuswowati, Murbangun; Kadarwati, Sri; Susilaningsih, Endang (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2020)
Evaluation of the cloud computing training program for the teachers of integrated Islamic elementary school (SDIT) Al-Madina Semarang has been conducted with the facilitation of the Department of Chemistry lecturer as an instructor. The evaluation aimed was to measure the impact of training on increased knowledge and participants ‘ interest in implementing cloud computing technology. The evaluation Model in this study used a Goal-Oriented Approach (GOA). The instrument of knowledge aspect is compiled using a Likert scale with four options. The measured point includes the fundamental point of knowledge (5 items), after-activity experience (10 items), and collaborative Aspects of collaboration (4 items). The analysis of this study based on calculating the proportion of two criteria, i.e., low and high. 23 Participant Data eliminated to 17 based on completeness of instrument replenishment. The data was analyzed by using percentages. From the initial knowledge side, 12 of 17 entry categories are low. In contrast, 17 out of 17 participants feel confident about implementing cloud computing technology. The strength documents are sent to achieve a result of 100% both in terms of completeness and quantity. While the interest to collaborate gained a result of 12 out of 17 have a strong desire. All activities that have been carried out can be concluded that computing training programCOMPUTING TRAINING PROGRAM has succeeded in increasing the knowledge of participants to manage collaborative learning documents activities succeeded in increasing the knowledge of participants.